Hollow fibers and methods for their preparation

JP7644784B2Active Publication Date: 2025-03-12AQUAPORIN AS
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2022581400
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-06-29
Filing Date
2021-06-25
Publication Date
2025-03-12
Estimated Expiration
2041-06-25

AI Technical Summary

Benefits of technology

【0009】 ボア水溶液中にPEIを添加することにより、PAIとPEIを反応させて中空繊維膜の内腔(内面)にガター層とも呼ばれる内表面層を形成することができる。内表面層は、TFC層をPAI支持層に付着させるためのプライマーとして機能する。したがって、内表面層があることで高い接着性を確保し、TFC層の剥離を防ぐことができる。さらに、PEIはアミン基を含み、これらの基がジ-およびトリアミン化合物と共にTFC層の形成に関与し、それによってTFC層がガター層を介してPAI支持層に共有結合を形成すると推測される。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007644784000028
    Figure 0007644784000028
  • Figure 0007644784000029
    Figure 0007644784000029
  • Figure 0007644784000030
    Figure 0007644784000030
Patent Text Reader

Abstract

Disclosed herein is a method for preparing a hollow fiber, the method comprising the steps of: providing a dope solution comprising polyamideimide (PAI); providing an aqueous bore solution comprising polyethyleneimine (PEI); extruding the dope solution into a cross-sectional ring shape and expelling the bore solution at the center of the ring shape; reacting the PAI and PEI, thereby forming an inner surface layer comprising a cross-linked reaction product; and forming a polyamide thin film composite (TFC) layer on the inner surface layer comprising the cross-linked reaction product by an interfacial reaction of an aqueous di- or triamine compound with an organic di- or triacyl halide compound.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to hollow fibers, their preparation methods, and hollow fiber modules including hollow fiber bundles, which have a high degree of integration between the support membrane and the selective layer, ensuring physical stability under a variety of conditions. [Background technology]

[0002] Hollow fiber modules are becoming increasingly popular for forward osmosis (FO). The FO process uses an osmotic gradient as the driving force instead of hydraulic pressure used in reverse osmosis (RO), and therefore has the potential to extract water with less energy consumption. FO is suitable for a wide range of applications, including wastewater treatment, water purification, desalination, food and beverage, and power generation.

[0003] In the food and beverage sector, WO2019215226 proposes the use of hollow fibre modules to increase the ethanol concentration in ethanolic liquids such as beer and wine. Other new areas include the concentration of liquid coffee before freeze drying or spray drying, coconut water concentration and fruit juice concentration.

[0004] The hollow fiber modules are also suitable for reverse osmosis (RO) operations, such as low pressure RO. Hollow fiber modules used in low pressure RO operations are useful, for example, in producing drinking water from impure sources.

[0005] Hollow fibers are commonly produced by hollow fiber spinning, particularly dry-jet wet spinning, as disclosed, for example, in Shi et al. (J Membrane Sci. 305 (2007) pp. 215-225).

[0006] WO2012074487 relates to a method of forming a hollow fiber membrane comprising a polyamideimide (PAI) hollow fiber substrate having a polyethyleneimine (PEI) cross-linked PAI surface layer, the membrane being suitable for forward osmosis applications. The method comprises contacting an exterior PAI hollow fiber substrate with an aqueous solution of polyethyleneimine (PEI) under conditions suitable for cross-linking the PAI in the surface layer of the PAI hollow fiber substrate with PEI. Summary of the Invention [Problem to be solved by the invention]

[0007] It is an object to provide a robust hollow fiber with high physical integrity, in particular to obtain high adhesion between the support membrane and the selective layer so that delamination is avoided or reduced, and it is further an object of the present invention to provide a membrane with low support defects, i.e. defects in the selective layer due to the surface topology of the hollow fiber. [Means for solving the problem]

[0008] The present invention provides in a first aspect a method for preparing a hollow fiber, comprising the steps of: a) providing a dope solution including polyamideimide (PAI); b) providing an aqueous bore solution containing polyethyleneimine (PEI); c) extruding the dope solution into a cross-sectional annular shape and discharging the bore solution at the center of the annular shape; d) reacting the PAI with the PEI, thereby forming an inner surface layer comprising a cross-linked reaction product; e) forming a polyamide thin film composite (TFC) layer on the inner surface layer containing the crosslinked reaction product by interfacial reaction of an aqueous di- or triamine compound with an organic di- or triacyl halide compound; The present invention relates to a method comprising the steps of:

[0009] By adding PEI to the bore aqueous solution, the PAI and PEI can react to form an inner surface layer, also called the gutter layer, on the lumen (inner surface) of the hollow fiber membrane. The inner surface layer acts as a primer to attach the TFC layer to the PAI support layer. Thus, the presence of the inner surface layer ensures high adhesion and prevents the TFC layer from peeling off. In addition, PEI contains amine groups, and it is speculated that these groups, together with the di- and triamine compounds, participate in the formation of the TFC layer, thereby forming a covalent bond between the TFC layer and the PAI support layer through the gutter layer.

[0010] In some embodiments of the present invention, the gutter layer tends to even out the surface roughness often observed on the inner surface of hollow fibers. The smooth surface provided by the gutter layer thus reduces support defects, i.e., defects in the TFC layer due to height variations in the surface topology.

[0011] In some embodiments of the present invention, a smooth gutter layer slows down the diffusion rate of the di- or triamine compound during the formation of the interfacial reaction, ensuring a thinner and / or denser TFC layer.

[0012] According to a second aspect, there is provided a hollow fiber comprising an outer support layer, an inner surface layer, and a polyamide thin film composite (TFC) layer, wherein the outer support layer comprises polyamideimide (PAI), the inner surface layer comprises a reaction product of PAI and polyethyleneimine (PEI), and the TFC layer comprises a reaction product of a di- or triamine compound and a di- or triacyl halide compound.

[0013] According to a third aspect of the present invention there is provided a hollow fibre module comprising a bundle of hollow fibres according to the second aspect.

[0014] These and other objects are achieved by means of the features of the independent claims. Further embodiments are evident from the dependent claims, the description and the drawing.

[0015] In a possible embodiment of the first aspect, the monomer of the PAI has the following chemical structure:

[0016] [ka]

[0017] [In the formula, Ar is

[0018] [ka]

[0019] is an aromatic group selected from has.

[0020] In a possible embodiment of the first aspect, the dope solution further comprises an aprotic solvent.

[0021] In a possible embodiment of the first aspect, the aprotic solvent is selected from the group consisting of N-methylpyrrolidone (NMP), dimethylacetamide (DMAC), dimethylsulfoxide (DMSO) and dimethylformamide (DMF), or a mixture thereof.

[0022] In a possible embodiment of the first aspect, the dope solution further comprises a polymer selected from the group consisting of polyphenylsulfone (PPSU), polyethersulfone (PES), sulfonated polyethersulfone (SPES) polysulfone (PSU), polyetheretherketone (PEEK), high temperature sulfone resin, self-reinforced polyphenylene, polybenzimidazole (PBI), polyimide (PI), polyetherimide (PEI), polyphenylene sulfide (PPS) and mixtures thereof.

[0023] In a possible embodiment of the first aspect, the solution viscosity of the PAI measured in 25% NMP at 40° C. is 30,000 cP or less.

[0024] In a possible embodiment of the first aspect, the dope solution further comprises a glycol.

[0025] In a possible embodiment of the first aspect, the glycol is selected from ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, glycerol or polyethylene glycol (PEG). Typically, the PEG has a molecular weight of 10,000 D or less, such as PEG 200, PEG 400, etc.

[0026] In a possible embodiment of the first aspect, the PEI of the bore aqueous solution has an average molecular weight (Mw) of 2,000 g / mol or more, such as 25,000 g / mol or more, preferably 100,000 g / mol or more.

[0027] In a possible embodiment of the first aspect, the PEI is branched.

[0028] In a possible embodiment of the first aspect, the aqueous bore solution further comprises an aprotic solvent.

[0029] In a possible embodiment of the first aspect, the aprotic solvent is selected from the group consisting of N-methylpyrrolidone (NMP), dimethylacetamide (DMAC), dimethylsulfoxide (DMSO), and dimethylformamide (DMF), or a mixture thereof.

[0030] In a possible embodiment of the first aspect, step c) is carried out by dry jet wet spinning.

[0031] In a possible embodiment of the first aspect, the nascent hollow fiber after extrusion travels through an air gap before solidifying in the non-solvent.

[0032] In a possible embodiment of the first aspect, the air gap is between 5 and 40 cm.

[0033] In a possible embodiment of the first aspect, a plurality of hollow fibers are assembled into a module before the polyamide TFC layer is prepared.

[0034] In a possible embodiment of the first aspect, the di- or triamine compound is selected from m-phenylenediamine (MPD), diethylenetriamine, dipropylenetriamine, phenylenetriamine, bis(hexamethylene)triamine, bis(hexamethylene)triamine, bis(3-aminopropyl)amine, hexamethylenediamine, N-tallow alkyldipropylene, 1,3,5-triazine-2,4,6-triamine and mixtures of these compounds.

[0035] In a possible embodiment of the first aspect, the di- or triacyl halide compound is selected from trimesoyl chloride (TMC), trimesoyl bromide, isophthaloyl chloride (IPC), isophthaloyl bromide, terephthaloyl chloride (TPC), terephthaloyl bromide, adipoyl chloride, cyanuric chloride and mixtures of these compounds.

[0036] In a possible embodiment of the first aspect, the aquaporin water channels are incorporated into the TFC layer.

[0037] In a possible embodiment of the first aspect, the aquaporin water channels are assembled into nanostructures comprising polyethyleneimine.

[0038] In a possible embodiment of the first aspect, the polyethyleneimine has an average molecular weight between about 2,000 Da and about 10,000 Da, for example between about 3,000 Da and about 5,000 Da.

[0039] In a possible embodiment of the first aspect, the aquaporin water channels are solubilized with a detergent prior to assembly into the polyethylenimine-containing nanostructure.

[0040] In a possible embodiment of the first aspect, the detergent is selected from the group consisting of lauryl dimethylamine N-oxide (LDAO), octyl glucoside (OG), dodecyl maltoside (DDM) or a combination thereof.

[0041] In a possible embodiment of the first aspect, the aquaporin water channels are provided in the vesicle prior to incorporation into the TFC layer.

[0042] In a possible embodiment of the first aspect, the vesicle comprises an amphiphilic diblock copolymer of the PMOXA-PDMS type and a reactive end group functionalized PDMS.

[0043] In a possible embodiment of the first aspect, the PMOXA-PDMS is PMOXA 10-40 -PDMS 25-70 and mixtures thereof.

[0044] In a possible embodiment of the first aspect, the mixture is of the general formula PMOXA 10-28 -PDMS 25-70 and a first amphiphilic diblock copolymer of the general formula PMOXA 28-40 -PDMS 25-70 and a second amphiphilic diblock copolymer of

[0045] In a possible embodiment of the first aspect, said reactive end group functionalized PDMS is functionalized with one or more of amine, carboxylic acid, and / or hydroxy groups.

[0046] A possible embodiment of the first aspect further comprises a triblock copolymer of the PMOXA-PDMS-PMOXA type.

[0047] In a possible embodiment of the first aspect, the TFC layer is present on the inside of the fiber.

[0048] In a possible embodiment of the second aspect, the outer support layer further comprises a polymer selected from the group consisting of polyphenylsulfone (PPSU), polyethersulfone (PES), polysulfone (PSU), polyetheretherketone (PEEK), high temperature sulfone resin, self-reinforced polyphenylene, polybenzimidizole (PBI), polyimide (PI), polyetherimide (PEI), polyphenylene sulfide (PPS), and mixtures thereof.

[0049] In a possible embodiment of the second aspect, the solution viscosity of the PAI measured in 25% NMP at 40° C. is 30,000 cP or less.

[0050] In a possible embodiment of the second aspect, the PEI has an average molecular weight (Mw) of 100,000 g / mol or more.

[0051] In a possible embodiment of the second aspect, the PEI is branched.

[0052] In a possible embodiment of the second aspect, the di- or triamine compound is selected from m-phenylenediamine (MPD), diethylenetriamine, dipropylenetriamine, phenylenetriamine, bis(hexamethylene)triamine, bis(hexamethylene)triamine, bis(3-aminopropyl)amine, hexamethylenediamine, N-tallow alkyldipropylene, 1,3,5-triazine-2,4,6-triamine and mixtures of these compounds.

[0053] In a possible embodiment of the second aspect, the di- or triacyl halide compound is selected from trimesoyl chloride (TMC), trimesoyl bromide, isophthaloyl chloride (IPC), isophthaloyl bromide, terephthaloyl chloride (TPC), terephthaloyl bromide, adipoyl chloride, cyanuric chloride and mixtures of these compounds.

[0054] In a possible embodiment of the second aspect, the aquaporin water channels are incorporated into the TFC layer.

[0055] In a possible embodiment of the second aspect, the aquaporin water channels are assembled into nanostructures comprising polyethyleneimine.

[0056] In a possible embodiment of the second aspect, the polyethyleneimine has an average molecular weight between about 2,000 Da and about 10,000 Da, for example between about 3,000 Da and about 5,000 Da.

[0057] In a possible embodiment of the second aspect, the aquaporin water channels are solubilized in detergent prior to assembly into the polyethylenimine-containing nanostructure.

[0058] In a possible embodiment of the second aspect, the detergent is selected from the group consisting of lauryl dimethylamine N-oxide (LDAO), octyl glucoside (OG), dodecyl maltoside (DDM) or a combination thereof.

[0059] In a possible embodiment of the second aspect, the aquaporin water channels are provided in a vesicle.

[0060] In a possible embodiment of the second aspect, the vesicle comprises an amphiphilic diblock copolymer of the PMOXA-PDMS type and a reactive end group functionalized PDMS.

[0061] In a possible embodiment of the second aspect, the PMOXA-PDMS is 10-40 -PDMS 25-70 and mixtures thereof.

[0062] In a possible embodiment of the second aspect, the mixture is a compound represented by the general formula PMOXA 10-28 -PDMS 25-70 and a first amphiphilic diblock copolymer of the general formula PMOXA 28-40 -PDMS 25-70 and a second amphiphilic diblock copolymer of

[0063] In a possible embodiment of the second aspect, the reactive end group functionalized PDMS is functionalized with one or more of amine, carboxylic acid, and / or hydroxy groups.

[0064] A possible embodiment of the second aspect further comprises a triblock copolymer of the PMOXA-PDMS-PMOXA type.

[0065] In a possible embodiment of the second aspect, the wall thickness of the hollow fibre is 0.10±0.01 mm or more.

[0066] In a possible embodiment of the second aspect, the hollow fibre has an inner diameter of 0.80±0.01 mm or more.

[0067] In a possible embodiment of the second aspect, the porosity of the hollow fibres is 75% or more.

[0068] In a possible embodiment of the third aspect, the hollow fiber module includes a shell around a bundle of hollow fibers and an inlet and an outlet connected to the lumen of the hollow fibers at each end of the bundle for passing a first solution to the lumen side of the module, and an inlet and an outlet are provided in the shell for passing a second solution to the shell side of the module.

[0069] In a possible embodiment of the third aspect, the hollow fiber bundles are potted at each end of the module to form a liquid-tight seal between the outer surface of the hollow fibers and the shell.

[0070] These and other aspects will be apparent from and elucidated with reference to the embodiments described hereinafter. [Brief description of the drawings]

[0071] [Figure 1] Figure 1 shows SEM images of bare and M0.12 fibers: a) cross-section, b) inner surface before IP coating, and c) inner surface after IP coating. [Diagram 2] FIG. 2 shows the burst pressure of the fiber substrate versus wall thickness (t) normalized by OD (outer diameter) (n=5). [Diagram 3] FIG. 3 shows the zeta potential of the hollow fiber support as a function of pH. (Bars represent standard deviation for three fibers, each measured six times.) [Figure 4] FIG. 4 shows the pure water permeability of the fiber support (before IP coating) (n=3). [Figure 5A] FIG. 5 shows in 5A the NaCl rejection as a function of water permeability (A) (n=3) and in 5B the TSC rejection as a function of (A) (n=3). [Figure 5B] Same as above. [Figure 6A] FIG. 6 shows in 6A the water flux (Jw) and reverse salt flux (Js) measured in FO mode using DI water as the feed solution and 1M NaCl as the draw solution (n=3), and in 6B the water flux (Jw) and reverse salt flux (Js) measured in FO mode using DI water as the feed solution and 1M TSC as the draw solution (n=3). [Figure 6B] Same as above. [Figure 7A] FIG. 7 shows the S-parameters measured in FO mode and calculated by equation (5) for left) 1M NaCl, and right) 1M TSC, n=3. [Figure 7B] Same as above. [Figure 8] Figure 8 shows SEM images of the unmodified and 750K fibers: (a) cross-section, (b) middle section morphology, (c) inner surface before IP, and (d) inner surface after IP. [Figure 9] Figure 9 shows cross-sectional images comparing the freshly spun fiber (750K) with a fiber from Chapter 5 (M0.12) spun with 3 wt% more polymer. [Figure 10] Figure 10 shows the zeta potential of the inner surface of the HF support as a function of pH (n=12). (M0.12 was spun with 3 wt% more polymer content, data from Chapter 5 are used for comparison.) [Figure 11]Figure 11 shows the PWP of the substrates (n=3) measured in an inside-out, dead-end configuration at 1 bar (M0.12 was spun with 3 wt% more polymer content, data from Chapter 5 is used for comparison). [Figure 12] Figure 12 shows the individual data of NaCl rejection of the fibers after IP coating at 2 bar with 500 mg L-1 NaCl solution versus water permeability measured at 2 bar with DI water. (M0.12 was spun with 3 wt% more polymer content, data from Chapter 5 are taken for comparison.) [Figure 13] Figure 13 shows the permeation performance of HF membranes in FO mode using 1 M NaCl as draw solution and DI water as feed solution. Left y-axis / bars: water flux. Right y-axis / squares: reverse salt flux, n=3. (M0.12 was spun with 3 wt% more polymer content, data from Chapter 5 are taken for comparison.) [Figure 14] Figure 14 shows the permeation performance of HF membranes in PRO mode using 1M NaCl as draw solution and DI water as feed solution. Left y-axis / bars: water flux. Right y-axis / squares: reverse salt flux, n=3. (M0.12 is spun with 3 wt% more polymer content, data from Chapter 5 are taken for comparison.) [Figure 15] Figure 15 shows the structural parameters of the HF membrane in FO and PRO modes using 1 M NaCl as the draw solution and DI water as the feed solution (n=3). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0072] Hollow fibers are generally produced by a process called dry jet wet spinning, where a dope solution is extruded through a spinneret together with a bore fluid. The dope solution is extruded from a ring-shaped dual orifice spinneret, and the bore solution is extruded from the center of the ring. The dual orifice spinneret contains an annular outer die gap for the dope solution and a central die gap for the bore solution. The spun hollow fiber passes through a certain air gap distance and then enters a coagulation bath, where solid hollow fibers are formed by phase separation with a non-solvent.

[0073] The PAI of the nascent hollow fiber is modified after extrusion by reaction with the PEI present in the bore solution. More specifically, the carbonyl groups of the PAI react with the amine groups of the PEI to form a cross-linked polymer. After a certain reaction time, the nascent hollow fiber is coagulated in a coagulation bath.

[0074] The PAI support layer modified with the internal crosslinked reaction product of PAI and PEI is further modified by forming a thin film composite (TFC) layer by interfacial polymerization. The TFC layer can be prepared using an amine reactant, preferably an aromatic amine, such as a diamine or triamine, e.g., 1,3-diaminobenzene (m-phenylenediamine-MPD), in an aqueous solution, and an acyl halide reactant, such as a diacid or triacid chloride, preferably an aromatic acyl halide, e.g., benzene-1,3,5-tricarbonyl chloride (TMC), dissolved in an organic solvent, where the reactants are combined in an interfacial polymerization reaction.

[0075] The amine groups of the di- or tri-amine compound and the amine groups of the PEI compete for reaction with the acyl halide groups of the acyl halide compound, and therefore the TFC layer is believed to be covalently bonded to the PAI support membrane through the gutter layer.

[0076] PAIs are thermoplastic amorphous polymers with a positive synergy of the properties of both polyamides and polyimides, and therefore have excellent mechanical, thermal, and chemical resistance properties. Due to their ability to form intrachain and interchain hydrogen bonds, PAIs exhibit good chemical stability over a wide pH range and are highly resistant to many organic solvents. In addition, PAIs can be utilized in the manufacture of hollow fiber membranes using non-solvent induced phase separation (NIPS) technology. PAIs are primarily manufactured by Solvay Advanced Polymers under the trademark Torlon (Torlon®). There are three types of Torlon® PAI materials that are particularly useful for membrane manufacture: Torlon® 4000T-LV (low viscosity), Torlon® 4000T-MV (medium viscosity), Torlon® 4000T-HV (high viscosity), and a finer particle size version, Torlon® 4000TF. In one embodiment, Torlon® 4000T-TF is used in the present invention. Torlon® PAI powders are soluble in dipolar aprotic solvents such as N-methylpyrrolidone (NMP), dimethylacetamide (DMAC), dimethylsulfoxide (DMSO), and dimethylformamide (DMF). Torlon® 4000T-TF appears as a fine yellow powder with a solution viscosity of 7,000 cP in 25% NMP measured at 40°C.

[0077] Although the membrane is expected to function and perform the forward osmosis process for any of the semipermeable membranes mentioned above, water flux is generally more efficient when aquaporin water channels are incorporated into the TFC layer. Aquaporin water channels are transmembrane proteins found widely in nature that selectively transport water in and out of cells. In industrial settings, aquaporin water channels in semipermeable membranes ensure the flow of water by osmosis while other solutes in the solution are excluded. Thus, when aquaporin water channels are active, they help the semipermeable membrane to exclude solutes and facilitate the permeation of water through the membrane.

[0078] Aquaporin water channels are incorporated into the membrane with at least a significant amount of the molecules in an active conformation. According to one aspect of the present invention, when aquaporin water channels are assembled into nanostructures that include polyalkyleneimines, such as polyethyleneimine, the activity of the aquaporin water channels is maintained. As explained in more detail in WO17137361, which is incorporated herein in its entirety, polyalkyleneimines, such as polyethyleneimine (PEI), form self-assembled nanostructures with transmembrane proteins, such as aquaporin water channels. This nanostructure ensures that the aquaporin water channels remain at least partially active after being incorporated into the TFC layer. It is currently believed that the polymer interacts with the transmembrane proteins to prevent them from reacting with the monomers involved in the formation of the TFC layer. Furthermore, it is currently believed that the PEI of the aquaporin nanoparticles integrates into the gutter layer by reacting with the PAI.

[0079] Generally, PEI is a substantially linear or branched polymer having an average molecular weight between about 2,000 Da and about 10,000 Da, for example between about 3,000 Da and about 5,000 Da. It is currently believed that the relatively short polymers interact with transmembrane proteins to prevent them from reacting with monomers involved in the formation of the TFC layer, while at the same time not substantially inhibiting their interaction with water.

[0080] To prevent aggregation of aquaporin water channels, it may be advantageous to solubilize the aquaporin water channels with detergents before assembly into nanostructures containing polyalkyleneimines. Aquaporin water channels naturally occur in cell membranes, so the proteins display hydrophobic domains on the surface. It is believed that the hydrophobic domains of the detergent interact with the hydrophobic domains of the aquaporin water channels to form solubilized proteins. Aquaporin water channels can be solubilized by a number of detergents, but it is currently preferred to use detergents selected from the group consisting of LDAO, OG, DDM, or combinations thereof.

[0081] In another embodiment of the present invention, the aquaporin water channel is provided in a vesicle prior to incorporation into the TFC layer. The vesicle is the natural environment for the aquaporin water channel, and the vesicle can be formed by several different membrane-forming materials, including naturally occurring phospholipids. In one embodiment of the present invention, the vesicle is formed of an amphiphilic diblock copolymer, such as poly(2-methyloxazoline)-block-poly(dimethylsiloxane) diblock copolymer (PMOXA-PDMS) and reactive end group functionalized poly(dimethylsiloxane) (PDMS). As described in more detail in WO2018 / 141985, which is incorporated herein in its entirety, the above components self-assemble into a vesicle in the liquid composition.

[0082] The two blocks of the PMOXA-PDMS diblock copolymer may be of different lengths. To obtain sufficient stability of the vesicles, the PMOXA-PDMS diblock copolymer is usually 10-40 -PDMS 25-70 and mixtures thereof. Experiments have shown that mixtures of different PMOXA-PDMS diblock copolymers exhibit greater robustness. In a preferred embodiment, the vesicles are therefore selected from the group consisting of PMOXA 10-28 -PDMS 25-70 and a first amphiphilic diblock copolymer of the general formula PMOXA 28-40 -PDMS 25-70 and a second amphiphilic diblock copolymer of the formula (I). The weight ratio of the first amphiphilic diblock copolymer to the second amphiphilic diblock copolymer is usually in the range of 0.1:1 to 1:0.1. The concentration of the amphiphilic diblock copolymer in the liquid composition is generally in the range of 0.1 to 50 mg / ml, for example, 0.5 to 20 mg / ml, and preferably 1 to 10 mg / ml.

[0083] The reactive end-group functionalized PDMS (reactive end-group functionalized poly(dimethylsiloxane)) of the vesicle can be functionalized with one or more of amine, carboxylic acid, and / or hydroxyl groups. In one embodiment of the invention, the reactive end-group functionalized PDMS e-f bis(aminoalkyl), bis(hydroxyalkyl), or bis(alkyl carboxylate) terminated PDMS e-f For example, poly(dimethylsiloxane), bis(3-aminopropyl) or poly(dimethylsiloxane), bis(3-hydroxypropyl). Suitably, the integer e is selected in the range of 20 to 40, for example 30, and the integer f is selected in the range of 40 to 80, for example 50. Furthermore, the reactive end group functionalized PDMS e-f H2N-PDMS 30-50 , HOOC-PDMS 30-50 , and HO-PDMS 30-50 and mixtures thereof. Prior to incorporating the vesicle into the aquaporin water channel, the vesicle may be present in a liquid composition, with the amount of PDMS preferably being about 0.05% to about 1% v / v.

[0084] The vesicles of the present invention may be prepared by mixing about 1% v / v to about 12% v / v of PMOXA to enhance their integrity. a-b -PDMS c-d -PMOXA a-b Typically, the vesicle contains about 8% v / v to about 12% v / v PMOXA. a-b -PDMS c-d -PMOXA a-b PMOXA triblock copolymers. a-b -PDMS c-d -PMOXA a-b Triblock copolymers of this type are usually PMOXA 10-20 -PDMS 25-70 -PMOXA 10-20 is selected from.

[0085] The vesicles of the present invention may further comprise a flux improver to increase the water flux or reduce the reverse salt flux. The flux improver may be selected from a large group of compounds, generally preferred as alkylene glycol monoalkyl ether alkylates, beta cyclodextrin, or polyethylene glycol (15)-hydroxystearate. The flux improver is usually present in an amount of 0.1% to 1% by weight of the liquid composition.

[0086] The vesicles of the present invention can be in a liquid composition before immobilization on a membrane such as a TFC layer provided on a support membrane. The liquid composition can include a buffer to stabilize the vesicles. Before the aquaporin water channel is mixed with other components, the transmembrane protein is suitably solubilized with a detergent. The vesicles in the liquid composition can further include a detergent or surfactant. The detergent can be selected from the group consisting of lauryl dimethylamine N-oxide (LDAO), octyl glucoside (OG), dodecyl maltoside (DDM) or a combination thereof.

[0087] Without wishing to be bound by any particular theory, it is believed that vesicles containing freely available reactive groups on the surface are not only physically incorporated or immobilized (adsorbed) in the TFC layer, but also chemically bonded, since the reactive free end groups, such as amino, hydroxyl, and carboxyl groups, participate in an interfacial polymerization reaction with acyl chlorides, such as trimesoyl chloride (TMC). In this manner, it is believed that the vesicles are covalently bonded in the TFC layer, resulting in a relatively high vesicle loading and, consequently, a high water flux through the membrane. It is further currently believed that the free end groups, such as amino and hydroxyl groups, can react with the carbonyl groups of the PAI to form a covalent bond between the vesicle and the supporting hollow fiber membrane. It is further believed that the covalent bonding of the vesicles in the TFC layer increases the stability and / or lifetime of aquaporin water channels and vesicles containing aquaporin water channels when incorporated into the selective membrane layer.

[0088] Vesicles can be prepared in liquid compositions incorporating aquaporin water channels, which are expressed as PMOXA a-b -PDMS c-d Solutions of amphiphilic diblock copolymers of the type, 0.05% to about 1% reactive end group functionalized PDMS e-f and stirring the mixture of aquaporin water channels. For best results, stirring is continued for 12-16 hours.

[0089] The preparation of a thin film composite layer immobilizing vesicles incorporating aquaporin water channels on a porous substrate membrane includes the steps of providing a mixture of vesicles in a liquid composition prepared as disclosed above and a diamine or triamine compound, coating the surface of a porous substrate membrane with the mixture, applying a hydrophobic solution containing an acyl halide compound, and interfacially polymerizing the aqueous solution with the hydrophobic solution to form a thin film composite layer. In an embodiment of the present invention, the hydrophobic solution further comprises a TFC layer modifier in an amount of 0.1-10% by volume. The TFC layer modifier has the purpose of increasing water flow and / or increasing the rejection rate of solutes. In a suitable embodiment, the TFC layer modifier is a C3-C8 carbonyl compound. In one example, the TFC layer modifier is selected from the group consisting of diethylene ketone, 2-pentanone, 5-pentanone, and / or cyclopentanone. EXAMPLES

[0090] Example 1 1.1.1 Materials Polyamide-imide (PAI) Torlon® 4000TF was kindly provided by Solvay Advanced Polymers and was used as the base polymer for the dope solution preparation. 1-Methyl-2-pyrrolidone (NMP) 99% was kindly provided by Acros Organics. Isopar E was kindly received from ExxonMobil Petroleum & Chemical BVBA (Belgium). 1,3-Phenylenediamine (MPD) >98%, ethylene glycol (EG), glycerol 85–87%, 1,3,5-benzenetricarbonyl trichloride (trimesoyl chloride) (TMC) >98%, trisodium citrate (TSC) and polyethyleneimine (PEI, Mw ca. 750,000 g mol -1 (50 wt % aqueous solution of) was purchased from Sigma-Aldrich. All chemicals were used as received without further purification. 1.1.2 Fabrication of hollow fibers A dope composition consisting of 18 wt% PAI, 13 wt% EG and 69 wt% NMP was selected after several development stages. To enhance the subsequent interfacial polymerization step, the lumen side of the hollow fibers was modified using PEI in a one-step process during hollow fiber spinning.

[0091] Prior to the preparation of the dope solution, the base polymer (PAI) was dried in a drying oven at 100 °C for 24 h. After all compounds were added to a mixing bottle, both the bore and dope solutions were prepared using a roller bench. Degassing of the dope was performed by placing the polymer solution in the dope vessel of the spinning machine for 24 h. To investigate the effect of PEI modification, two different bore aqueous solutions were utilized, one with and one without PEI (Table 1).

[0092] [Table 1]

[0093] In total, seven different fibers were spun by dry-jet wet spinning (Table 2). The first batch was made with bore solution 1 (B1) and served as a reference for further analysis (bare). The other six fibers were made with bore solution 2 (B2) and varying the spinning conditions to obtain different wall thicknesses. The freshly spun fibers were washed with deionized (DI) water for 48 h, followed by immersion in a 30% w / w glycerol solution in water for 24 h and then dried.

[0094] [Table 2]

[0095] 1.1.3 Preparation of the module For filtration experiments, five fibers were placed each time inside a 10 mm perfluoroalkoxy (PFA) tube connected with two QST-10 Festo push-in fittings on each side. Both ends were potted with slow-curing epoxy resin to a length of 4.5 cm to give a fiber length of 16 cm. For each type of fiber, three modules were prepared for further experiments. 1.2 Membrane characterization 1.2.1 Scanning electron microscope observation The hollow fibers were first frozen in liquid nitrogen and then fractured to prepare cross-sectional samples. To analyze the luminal surface, the fibers were cut obliquely with a sharp razor blade. All samples were stored in a vacuum oven at 30 °C for 24 h. Finally, a 10 nm layer of chromium was sputter-coated on the sample surface using a Quorum Q150T ES sputter coater. Cross-sectional and luminal surface images of the samples were obtained by a scanning electron microscope JEOL JSM-6010LA. 1.2.2 Mechanical strength The burst pressure of the single fibre was determined with a custom setup from Convergence Industry BV, The Netherlands. This device forces a fluid through the hollow fibre with continuously increasing pressure until the sample breaks. This final pressure is reported. For this purpose, a single fibre membrane module was fabricated with the same configuration as the module used in the filtration experiments. Pressure was applied from the inside of the membrane at 0.5 bar per second. The fluid used was glycerol, which has a high viscosity and therefore low permeation, making it easy to control the pressure. The experiments were carried out at room temperature.

[0096] At the final pressure, the tensile strength (δ) of the fiber was determined from Barlow's equation shown in Equation (2).

[0097]

number

[0098] where P is the resulting burst pressure (bar), t is the wall thickness (mm), and D out is the outside diameter (mm) and δ is the tensile strength (bar). 1.2.3 Porosity measurement The porosity was measured using the known density of polyamideimide. The sample was first placed in a vacuum oven for at least 1 hour and then weighed. The porosity can be calculated using equation (3):

[0099]

number

[0100] m is the mass of the sample (g), ρ is the PAI density (g cm -3 ), V is the volume of the fiber (cm -3 ) The density of the polyamide-imide used in this calculation is 1.4 g cm -3 Three tests were performed for each type of fiber. 1.2.4 Determination of Zeta Potential The zeta potential of the fibers was determined at different pH (3-11) using 5 mM KCl as electrolyte solution with an electrokinetic SurPASS analyzer (Anton Paar, Graz Austria). In addition to the bare and one-step modified fibers, an additional post-modified fiber with PEI (Post-M) was tested. For the preparation of Post-M fibers, three bare fibers were dip-coated in a 1 wt% PEI solution at pH 5.8 for 12 h. This was done to show the surface charge of pure PEI for comparison purposes.

[0101] For the zeta potential measurements, three single fibers of each type were potted separately in 7 cm long tubes and measurements were performed in triplicate. The pH was automatically adjusted using two solutions, 0.1 M HCl and 0.1 M NaOH. The zeta potential was calculated using equation (4):

[0102]

number

[0103] Here, ζ is the zeta potential (V), I is the streaming current (A), P is the pressure (Pa), η is the dynamic viscosity of the electrolyte solution (Pa s), ε is the dielectric constant of water, and ε0 is the dielectric constant in a vacuum (F m -1 ), L s is the channel length (m), A s is the cross-sectional area of ​​the flow channel (m 2 ). 1.2.5 Pure water transmittance measurement Pure water permeability of the fiber PWP (L m -2 h -1 bar -1 ) was determined using nitrogen pressure at 2 bar in a dead-end, inside-out configuration.

[0104]

number

[0105] where V is the volume of the collected permeate (L), t is the collection time (h), and A is the membrane inner surface area (m 2), ΔP is the pressure difference (bar) between the lumen and shell of the hollow fiber. 1.2.6 Interfacial polymerization Interfacial polymerization (IP) was performed on the inner surface of the fibers using MPD and TMC to form a polyamide (PA) selective layer. To achieve sufficient wetting and glycerol removal from the fibers, the modules were immersed in DI water overnight prior to the IP reaction. A 2.5% (w / v) MPD aqueous solution and a 0.15% (w / v) TMC solution were used for the IP coating. TMC was dissolved in Isopar E using an ultrasonic bath (20 °C, 2 min).

[0106] First, excess water on the shell and in the hollow fiber lumen was removed with a N2 flow for 1.5 min. Then, a syringe pump was used to flow 10 L min -1 The MPD solution was supplied to the lumen side of the vertically fixed fibers (five fibers) for 2 min at 400 rpm. The MPD solution was then held in the fibers in a horizontal position for 10 min, after which excess MPD was removed by N2 flow for 1 min. Next, the TMC solution was pumped at 10 L min -1 Two cycles of 15 s at 45 s intervals were introduced into the vertically fixed fiber. Residual TMC was then removed with N2 flow for 30 s, followed by drying in an air oven at 70 °C for 10 min. Finally, the lumen of the fiber was washed with 20 ml of DI water, and the module was kept in DI water at 7 °C until further use. 1.2.7 Salt rejection 500 mg L -1 The salt rejection of the fibers coated with NaCl and TSC solutions was determined in an inside-out cross-flow filtration system with a transmembrane pressure of 2 bar. The cross-flow velocity of each fiber was 1.7 m s -1 The rejection was determined by measuring the conductivity of the feed solution and the collected permeate and was calculated as follows:

[0107]

number

[0108] In this formula, R is the salt rejection rate (%), σ fis the conductivity of the feed solution (μS cm -1 ), σ p is the conductivity of the permeate (μS cm -1 ).

[0109] Salinity permeability (B) is the water flux J w (L m -2 h -1 ) and mass transfer coefficient (K) (L m -2 h -1 ) was used to determine the Leveque correlation for fully developed laminar velocity distribution in a pipe.

[0110]

number

[0111] 1.2.8 FO performance The permeation performance of the fibres was evaluated in feed-facing selective bed (FO) mode. The tests were carried out at 3 L h per module using 1 M NaCl or 1 M TSC as draw solution. -1 Cross-flow velocity (velocity in the lumen 2 m s -1 The experiment was carried out in a countercurrent configuration at 1000 s (corresponding to 1000 s). The experiment was carried out for 1 h and the amount of water transferred from the feed solution to the draw solution per membrane area per hour was measured, and the water flux (J w )(L m -2 h -1 ) was determined. s )(g m -2 h -1 ) was determined by measuring the increase in conductivity of the feed solution per unit area of ​​membrane per hour. The amount of solute passing through to the feed side was measured using a predefined calibration curve.

[0112] Since it is difficult to measure the degree of curvature, the structural parameter (S) is estimated by a fitting method, and the FO mode can be described as Eq. (8).

[0113]

number

[0114] Here, J w (L m -2 h -1 ) is the seepage flow, D(m 2 h -1 ) is the solute diffusivity, π D (bar) is the osmotic pressure of the draw solution, A is the water permeability (L m -2 h -1 Bar -1 ), B is the salt permeability coefficient (L m -2 h -1 ).

[0115] For all results presented, the errors presented are the standard deviation of the measurements obtained. 1.3 Results and Discussion 1.3.1 Hollow fiber dimensions and porosity The thickness, inner diameter, and porosity of the spun fibers can be seen in Table 3. The wall thickness of the fibers varied in the range of 0.07–0.17 mm. The measured porosity of the one-step modified fibers ranged from 75–77%. Based on equation (1), a 2% change in porosity would result in a 2% change in the S-parameter, but the difference in wall thickness used in this study (0.07–0.17 mm) could affect the S-parameter by 143%. From this, it was concluded that the effect of porosity in this study is very small compared to the wall thickness and can be neglected. Furthermore, when the effect of the porosity of these fibers on the S-parameter (determined by equation (7)) was analyzed, no true correlation was found (data not reported here).

[0116] [Table 3]

[0117] 1.3.2 Hollow fiber morphology For illustrative purposes, the SEM images of bare and M0.12 fibers are selected and shown in this chapter due to their similar wall thickness. Figure 1 shows the cross-sectional images and the inner surface images before and after IP coating. The cross-sectional images of bare and M0.12 fibers show similar morphologies. They have finger-like structures extending from the center to the lumen side, with some macrovoids next to the shell side. This indicates that the addition of PEI to the bore solution did not affect the overall structure of the HF support, and therefore a similar degree of tortuosity is expected for the fibers. This is advantageous in that the overall structure of the support can be further improved independently to meet specific requirements without modifying the inner surface. Nevertheless, the inner surface of the modified fiber (image M0.12-b) shows a slightly different structure than the bare fiber (image bare-b). In fact, it appears smoother compared to the lumen surface of the bare fiber. Similar structures can also be observed on the inner surfaces of other modified fibers with different thicknesses (Figure A3). This similarity in the inner surface images of all modified fibers indicates that the modification of the inner surface with PEI is reproducible, regardless of changes in the thickness of the support. This is important because IP is known to be sensitive to the physicochemical properties of the support surface, such as porosity, pore size, and hydrophilicity, and therefore, in order to focus solely on the thickness of the support, the bore surfaces need to be similar.

[0118] SEM images of the inner surface after IP clearly show the presence of a polyamide layer, but with a different morphology (images of Bare-c and M0.12-c) that can undoubtedly be attributed to the surface modification with PEI. The addition of PEI made the luminal surface smoother, which resulted in a thinner PA layer. Because of this, the reaction is mostly occurring inside the pores, not on the surface, whereas the opposite is true for the Bare fibers. In the Bare fibers, the MPD solution diffuses more easily out of the surface pores during the IP process, resulting in the interface between MPD and TMC being mostly on the surface. Because of this, a more pronounced ridge-and-valley PA layer was obtained for the Bare fibers (Bare-c). The same PA structure was observed in other PEI-modified fibers of various thicknesses (data not reported here), again indicating that the inner surface of the modified fibers is consistent with the change in wall thickness. 1.3.3 Mechanical strength The burst pressure of the modified fibers is plotted against the thickness normalized by the outer diameter (OD) (Figure 2). As expected from Equation 2 (Barlow's equation), a clear trend of increasing the burst pressure of the fibers was observed by increasing the wall thickness. This also indicates that reducing the wall thickness to improve the permeate water flux sacrifices the mechanical strength of the support. Nevertheless, a high burst pressure of 13 ± 1.5 bar was obtained for the thinnest fiber with a wall thickness of 0.07 mm, which is attributed to the high tensile strength of the PAI. We argue that a burst pressure of 10 bar is sufficient for the membranes used in FO, which is similar to the burst pressure of commercial ultrafiltration membranes, whose operating pressures are usually less than 1 bar. Thus, all membranes are mechanically suitable for use in FO processes.

[0119] Furthermore, the burst pressure of the PAI fibers is compared with commercial PES / PVP ultrafiltration and microfiltration fibers from NX Filtration BV (Figure 2). As can already be deduced from the higher tensile strength of PAI (>147 MPa) compared to PES (<90 MPa), the burst pressure results also prove that, at similar wall thicknesses, PAI fibers show significantly higher burst pressures. These results highlight the importance of preselecting the right polymer properties to enable suitable fibers in the support design of FO membranes. Especially when aiming for low structural parameters by reducing the thickness, the selection of the right polymer becomes crucial. 1.3.4 Zeta potential of hollow fiber support (before IP) The zeta potential of all fibers before applying the IP layer is plotted as a function of pH in Figure 3. For ease of visualization, the zeta potential of the modified fibers is shown in color and the bare fibers in black. For the modified fibers, almost the same trend in zeta potential was observed. They had a more positive zeta potential profile compared to the bare fibers. This difference clearly indicates the successful modification of the inner surface with positively charged PEI. However, the zeta potential of the modified fibers does not fully reflect the zeta potential expected from PEI alone. To understand this better, the zeta potential of bare fibers post-modified with PEI (called Post-M) is added to the plot. Comparing the surface charge of the Post-M fibers with that of the one-step modified fibers reveals the difference in their zeta potential. The Post-M fibers showed a positive charge in almost the entire pH range and an isoelectric point at a pH above 10, which is consistent with the pKa of PEI. In contrast, the zeta potential of the fibers modified during spinning clearly shows a lower isoelectric point. This difference in zeta potential between the one-step and post-modified fibers indicates that the PAI support also contributes to the final surface charge of the one-step modified fibers. The significant contribution of the PAI support to the surface charge indicates that the PEI added to the membrane via the bore fluid becomes integrated with the support by the one-step preparation. 1.3.5 Pure Water Permeability (PWP) and Salt Rejection The pure water permeability of the fiber support before IP coating was measured (Figure 4). Notably, a trend of decreasing pure water permeability was observed with increasing wall thickness of the modified fiber. This indicates that thickness has a clear effect on mass transport resistance through the support, since the thinnest thickness showed the highest water permeability (lowest resistance value). In particular, a lower resistance to mass transport is advantageous to mitigate the ICP that occurs within the support in the FO process. This is because a lower resistance allows for greater movement of the draw solute within the support, compensating for the ICP.

[0120] Bare fibers recorded higher PWP compared to modified fibers (M0.12) of comparable thickness. Despite slight differences in porosity (78.3% for bare vs. 76.1% for M0.12), the higher PWP of bare fibers is mainly due to the absence of PEI modification. M0.12 fibers clearly have more extra resistance to water transport due to the addition of PEI, effectively narrowing the pores. Clearly, the higher flux of bare supports is not due to higher porosity (78.3%) compared to M0.12 (76.1%), as no correlation was found between porosity and PWP. This is further evidence of the significant effect of wall thickness on mass transport in HF supports.

[0121] The NaCl and TSC rejection rates of the modified fibers after IP coating were measured in RO mode and plotted against the water permeability (A) in Figure 5A and Figure 5B, respectively. The first notable observation is that the IP-coated fibers generally showed better rejection rates for TSC than for NaCl, which may be attributed to the difference in the size of the solutes. Secondly, in both cases, the thinner fiber (M0.07) showed lower rejection rates, which may be due to layer defects resulting from its small thickness. Due to the thin wall thickness of M0.07, not enough reservoirs are available for IP coating and not enough monomers are available to participate in the reaction to obtain a defect-free layer for the IP protocol we used. This can be overcome by optimizing the IP coating technique to improve the rejection rate for such thin hollow fiber supports. Thus, the lower rejection rate of M0.07 may be due to selective layer defects. Finally, except for the M0.07 fiber, the remaining modified fibers showed high rejection rates for NaCl and TSC, more than 88% and more than 97%, respectively. These high rejection rates demonstrate the high success rate of IP coating and the presence of defect-free PA layer, which is a prerequisite for FO membranes.

[0122] It is noteworthy that no correlation was found between the wall thickness of the modified fibers after IP coating and the water permeability (A) of the selective layer. This indicates that the properties of the PA selective layer formed on all fibers are independent of their wall thickness. Thus, having the same PA selective layer on all modified fibers is actually preferred, as it can finally focus on the effect of the wall thickness of the support on the FO performance.

[0123] Furthermore, for all the membranes with different wall thicknesses, 1 (L m -2 h -1 Bar -1 A water permeability (A) of less than 0.01 mm was obtained, and the membrane was in the A-limited region. This means that the performance of the FO (permeation water flux) is affected by both the selective layer and the supporting layer. Therefore, it is expected that further optimization of the IP protocol can significantly improve the FO performance. 1.3.6 FO performance To investigate the role of wall thickness, the IP-coated modified fibers were tested in FO mode. In Figure 6, the permeation water flux (J w ) and reverse salt flux (Js) are plotted as a function of wall thickness. The osmotic water flux achieved with our FO membrane is lower than the typical values ​​reported for FO membranes, which is mainly due to its low A value. The A value can be increased to 1 (L m) by optimization of the IP coating procedure, which is not the aim of this study. -2 h -1 Bar -1 ), but even if only partially influenced by the A value, the effect of the wall thickness on the ICP (S parameter) is already evident and is only seen when A is greater than 1 (L m -2 h -1 Bar -1), it can be even more significant when the ICP is higher than 1000. It can be seen that the osmotic water flux increased by decreasing the wall thickness. This trend was theoretically expected from equation (1), the thinner the support, the lower the ICP and, consequently, the higher the osmotic water flux should be. The increasing trend was seen for both draw solutions, except for one case of M0.07 when 1M NaCl was used. The reason for this poorer result of M0.07 was the lower rejection rate for NaCl (66±3%), which resulted in a higher reverse salt flux in the FO process.

[0124] J w In addition, the reverse salt flux (Js) also showed a tendency to increase with decreasing wall thickness. Although high Js is not favorable for the FO process because of the loss of driving force, our modified fibers showed acceptable reverse salt flux, except for M0.07. However, this could be resolved by optimizing the IP coating, and eventually thinner supports could be coated appropriately.

[0125] Similarly, the measured S-parameters, as determined by the empirical method (Eq. (8)), showed the same trend. For both draw solutions, the S-parameters increased with increasing wall thickness (Fig. 7). In general, lower S-parameters were obtained when NaCl was used as the draw solution compared to TSC. Haese et al.

[44] found that S was larger with increasing valence of the draw solute ions (NaCl in this case compared to TSC). This finding indicates that the S-parameter of a support does not only depend on its physical properties (tortuosity, porosity, and thickness) but is also influenced by other parameters such as the properties of the draw solute. On the other hand, this finding of determining two different S-parameters for one and the same support may be due to the inaccuracy of the fitting equation (Eq. (8)) for estimating ICP. The inaccuracy of the existing structural parameter model (Eq. (8)) has been discussed before [2,45]. Regardless of these challenges, the results presented here clearly demonstrate the importance of the thickness of the support for FO membranes and clearly show that by choosing an appropriate polymer support with a very low thickness it is possible to fabricate one that still has the mechanical strength required for industrial applications. 1.4 Conclusion In this study, we systematically investigated the effect of hollow fiber wall thickness on membrane performance in forward osmosis (FO) mode. The inner surface of the support was simultaneously modified with PEI during spinning to better enable subsequent IP coating. After interfacial polymerization, the membranes showed high rejection rates for both NaCl and TSC, which are typical solutes in FO processes. To ensure membrane integrity when applied to FO processes, the mechanical strength of the hollow fibers was a critical aspect in the design of the membranes. By selecting PAI, a polymer with high tensile strength, we were able to fabricate very thin hollow fiber membranes, yet maintain burst pressures well above 10 bar for all membranes, which is more than sufficient for FO applications. We also revealed a correlation between fiber geometry, polymer tensile strength, and the burst pressure of the nascent fibers.

[0126] By reducing the wall thickness, the infiltration water flux increased from 1.2 ± 0.4 to 7 ± 1 (L m ) when 1 M TSC and 1 M NaCl were used as draws, respectively. -2 h -1 ), 2±0.4 to 7±2 (L m -2 h -1 ) significantly increased. The relatively low water flux even for the thinnest fiber may be attributed to the low water permeability (A) of the membrane after IP. It is expected that even higher fluxes can be obtained by further optimizing the IP and increasing the water permeability.

[0127] The results indicate that by using appropriate polymers and reducing the wall thickness of the support, the permeate flux can be significantly improved without compromising the mechanical strength, and therefore this type of thin hollow fiber support is a promising alternative to the thick RO-type supports that have been commonly used in FO membranes.

[0128] Example 2 2.1.1 Materials Polyamide-imide (PAI) Torlon® 4000TF was kindly provided by Solvay Advanced Polymers and was used as the base polymer for the dope solution preparation. Three molecular weights of branched polyethyleneimine (PEI) (PEI 750k: Mw ≈ 750,000 g mol -1 50% by weight solution; PEI 25k:Mw approx. 25,000g·mol -1 Pure solution; and PEI 2k: Mw approx. 2,000 g mol -150 wt% solution) was used in the bore fluid for the one-step modification of PAI hollow fiber supports. 1-Methyl-2-pyrrolidinone (NMP) 99% was purchased from Acros Organics. Isopar E was kindly provided by ExxonMobil Petroleum & Chemical BVBA (Belgium). 1,3-Phenylenediamine (MPD) >98%, ethylene glycol (EG), glycerol 85-87%, and 1,3,5-benzenetricarbonyl trichloride (TMC) >98% were purchased from Sigma-Aldrich. All chemicals were used as received without further purification. 2.1.2 Fabrication of hollow fibers The dope composition consisted of 15 wt% PAI, 16 wt% EG, and 69 wt% NMP, applying our dope recipe used in Example 1, which was configured to have 17% less polymer overall in the dope, or 3 wt% less PAI content. Before preparing the dope solution, the base polymer (PAI) was dried in an oven at 100°C for 24 hours. After all the compounds were added to the bottle, both the bore solution and the polymer solution (dope) were prepared on a roller bench. Degassing of the dope was performed by placing the polymer solution in the dope vessel of the spinner for 24 hours. Fibers were spun using a dry jet wet phase inversion spinning method.

[0129] Torlon (PAI) was chosen for its excellent mechanical properties and its potential for interaction with PEI, resulting in fibers with high burst pressure and proper adhesion of PEI to the support, respectively. PEI modification was performed to facilitate the application of subsequent interfacial polymerization by adding amines to the inner surface of the support.

[0130] To investigate the success of PEI modification, bore solutions without PEI were used in addition to bore containing PEI of different molecular weights (Table 1). A total of four types of fibers were spun in this study (Table 2). The first batch was made using bore B1 (unmodified) to use as a reference for further analysis, and the other three fibers were made using bore containing one of the different PEIs (B2, B3, B4).

[0131] [Table 4]

[0132] The nascent fibers were then washed with deionized (DI) water for 72 h, followed by post-treatment for 24 h by immersion in a 30% w / w glycerol solution to retain the pores upon drying. Finally, the fibers were hung to dry at room temperature until further use.

[0133] [Table 5]

[0134] The freshly spun fiber (Fiber 750K) is compared to a fiber that was spun with 3 wt% more polymer in the dope recipe (i.e., M0.12) and had its surface modified with 5 wt% PEI 750k. 2.1.3 Preparation of the module Five fibers were placed inside one 10 mm perfluoroalkoxy (PFA) tube and connected with two QST-10 Festo push-in fittings on either side. Both ends were potted with slow-curing resin (BISON, 2K Expert Polyurethane) to a length of 4.5 cm to give a fiber length of 16 cm. For each fiber type, three to four modules were prepared for further experiments. All filtration experiments were performed at least three times using separate modules. 2.2 Membrane characterization 2.2.1 Scanning electron microscopy The hollow fibers were frozen in liquid nitrogen and fractured to prepare cross-sectional samples for imaging. For preparation of the internal surface samples, the fibers were cut in half at an angle with a sharp razor blade. All samples were mounted in designated holders and stored in a vacuum oven at 30 °C for 24 h. Finally, they were sputter-coated with a 5 nm layer of platinum using a Quorum Q150T ES coater, followed by microscopy observations using a JEOL JSM-6010LA SEM. 2.2.2 Contact angle measurement To investigate the effect of PEI modification on the hydrophilicity of the support surface, the water contact angle of the inner surface was measured. To do so, hollow fiber supports were cut open and attached to double-sided tape so that the inner surface was exposed to the microsyringe of the analysis device (Figure 1). A 0.5 μL droplet of Di water was placed on the inner surface. The contact angle of the droplet was recorded after 3 s and analyzed by the software. The measurements were repeated three times at three different locations on each support. 2.2.3 Mechanical strength The burst pressure of the single fibre was determined with a custom setup from Convergence Industry BV, The Netherlands. This device forces a fluid through the hollow fibre at continuously increasing pressures until the sample breaks. This final pressure is reported. For this purpose, a single fibre membrane module was fabricated, similar to the module used in the filtration experiments. Pressure was applied from the inside of the membrane at 0.5 bar per second. The fluid used was glycerol, which has a high viscosity and therefore low permeability, making it easy to control the pressure. The experiments were carried out at room temperature.

[0135] At the final pressure, the tensile strength (δ) of the fiber was determined from Barlow's equation shown in Equation (1).

[0136]

number

[0137] where P is the resulting burst pressure (bar), t is the wall thickness (mm), and D out is the outside diameter (mm) and δ is the tensile strength (bar). 2.2.4 Porosity measurement The fibers were first washed in water for 20 minutes in an inside-out configuration and then stored in a vacuum oven at 30°C for at least 4 hours before testing. Porosity is measured using known values ​​of polyamideimide density. The samples are first placed in a vacuum oven for at least 1 hour and their weight is measured. Porosity can be calculated using equation (2):

[0138]

number

[0139] m is the mass of the sample (g), ρ is the PAI density (g cm -3 ), V is the volume of the fiber (cm -3 ) The density of the polyamide-imide used in this calculation is 1.4 g cm -3 Three tests were performed for each type of fiber. 2.2.5 Determination of Zeta Potential The zeta potential of the fibers was determined at pH (3-11) using a SurPASS electrokinetic analyzer (Anton Paar, Graz Austria) with 5 mM KCl as electrolyte solution. Two single fibers from each type were potted separately in 7 cm long tubes. The zeta potential was determined by flowing the electrolyte solution through the lumen of the fiber, and six measurements were taken for each pH setpoint for each fiber. The zeta potential value was then determined by averaging all 12 measurements at each pH. The pH was adjusted by automatic titration with 0.1 M HCl and 0.1 M NaOH. The zeta potential was calculated using equation (3):

[0140]

number

[0141] In this equation, ζ is the zeta potential (V), I is the streaming current (A), P is the pressure (Pa), η is the dynamic viscosity of the electrolyte solution (Pa s), ε is the dielectric constant of water, and ε0 is the dielectric constant in a vacuum (F m -1 ), Ls is the channel length (m), and As is the cross-sectional area of ​​the flow channel (m 2 ). 2.2.6 Pure water transmittance measurement Pure water permeability (PWP) of the fiber (A) (L m -2 h -1 Bar -1 ) was measured in dead-end, inside-out mode at 1 bar using compressed nitrogen.

[0142]

number

[0143] where V is the volume of the collected permeate (L), t is the collection time (h), and A is the membrane inner surface area (m 2 ), ΔP is the pressure difference (bar) between the lumen and shell of the hollow fiber. 2.2.7 Interfacial polymerization The inner surface of the fibers was coated by interfacial polymerization with MPD and TMC to form a polyamide (PA) selective layer. Prior to the reaction, all fiber modules were subjected to a PWP test in dead-end, inside-out mode at 1 bar to remove glycerol from the fibers. A 2.5% (w / v) MPD solution was prepared by dissolving the desired amount of MPD in DI water. TMC was dissolved in Isopar E using an ultrasonic bath (20 °C, 2 min) to obtain a 0.15% (w / v) TMC solution.

[0144] First, excess water in the lumen and shell side of the hollow fiber was removed by N2 flow for 1.5 min. Then, MPD solution was pumped at 10 L min -1 The solution was then held in the fiber in a horizontal position for 10 min, after which excess MPD was removed with N2 flow for 1 min. The TMC solution was then pumped at 10 L min -1 Two cycles of 15 s at 45 s intervals were delivered to the vertically fixed fiber. Afterwards, the residual TMC was removed with N2 flow for 30 s and then dried in an air oven at 70 °C for 10 min. Finally, the inner lumen of the fiber was washed with 20 ml of DI water and the module was kept in DI water at 7 °C for further use. 2.2.8 Salt rejection 500 mg L -1 The rejection of the fibers against a NaCl solution was determined in a cross-flow filtration system with a transmembrane pressure (TMP) of 2 bar. The rejection was calculated by measuring the conductivity of the feed solution and the collected permeate and using Eq. (5). The cross-flow velocity of each fiber was 1.7 m s -1 It was decided.

[0145]

number

[0146] In this formula, R is the salt rejection rate (%), σ f is the conductivity of the feed solution (μS cm -1 ), σ p is the conductivity of the permeate (μS cm -1 ). 2.2.9 Penetration performance The permeation performance of the fibers was evaluated in both FO (selective layer facing the feed solution) and PRO (selective layer facing the draw solution) modes. The tests were carried out at 3 L h per module using 1 M NaCl as the draw solution. -1 Cross-flow velocity (velocity in the lumen 2 m s -1 The experiment was carried out for 1 h and the permeate flux (J w )(L m -2 h -1 ) was determined by measuring the water transferred from the feed solution to the draw solution per unit area of ​​membrane per hour. Reverse salt flux (Js) (g m -2 h -1 ) was determined by measuring the conductivity of the feed solution per membrane area per time. The amount of solute passing through to the feed side was measured using a predefined calibration curve.

[0147] The structure parameter (S) is calculated in FO mode using equation (6):

[0148]

number

[0149] In the PRO mode, the estimation was performed by the fitting method using equation (7).

[0150]

number

[0151] Here, J w (L m -2 h -1 ) is the infiltration water flow rate, D(m 2 h-1 ) is the solute diffusivity, π D (bar) is the osmotic pressure of the draw solution, A (water permeability) (L m -2 h -1 Bar -1 ), B (salt permeability) (L m -2 h -1 ).

[0152] The salinity permeability (B) is calculated as the mass transfer coefficient (K) (L m) using the Leveque correlation

[37] for fully developed laminar velocity distribution in a pipe, following Yip et al.

[36] . -2 h -1 ) was decided.

[0153]

number

[0154] 2.3 Results and Discussion 2.3.1 Intrinsic properties of hollow fiber supports The intrinsic properties of the produced hollow fiber supports, such as dimensions, porosity, burst pressure, and contact angle, can be seen in Table 2.3. To better understand the role of the molecular weight of the PEI used, we tried to eliminate the effect of wall thickness on the FO performance by producing fibers of similar thickness. This is because the wall thickness can affect the permeate water flux (see Example 1), making it difficult to focus on the effect of molecular weight. The spun fibers with relatively thin wall thickness and open pore structure still showed a high burst pressure of about 14 bar on average. This is indeed due to the high tensile strength of polyamide-imide (Torlon). We claim that a burst pressure of 10 bar is sufficient for the membranes used in FO, similar to the burst pressure of commercial ultrafiltration membranes, whose operating pressure is usually less than 1 bar. Therefore, all membranes are mechanically suitable for use in FO processes. The change in the molecular weight of PEI did not affect the burst pressure and was not different from the unmodified support. The fibers also showed a porosity of more than 73%, indicating that the fibers are very open and suitable as FO supports. Indeed, in porous media, porosity above 75% also means low tortuosity, both of which are beneficial for low ICP and high infiltration water flux (see Example 1).

[0155] Here, to determine the effect of a 3 wt% reduction in polymer content on the intrinsic properties of the fiber, a comparison is made with the fiber of Example 1, which was spun with 3 wt% more polymer (i.e., M0.12). Through this example, we show that a 3 wt% reduction in polymer content is very well reflected in the fiber PWP, permeate water flux, S-parameter, and mechanical strength.

[0156] For example, a 3 wt% reduction in polymer is well reflected in the PWP results, with a 7 times higher PWP obtained for the freshly spun 750K. This higher PWP clearly indicates that the support is much more openable. Furthermore, the 3 wt% reduction also affected the burst pressure, which dropped from 18 bar to 14 bar, which is still sufficient for FO applications as mentioned earlier.

[0157] [Table 6]

[0158] All three modified supports (2K, 25K, 750K) showed lower contact angles than the unmodified support. This indicates that PEI contributes to the hydrophilicity of the inner surface. Indeed, the hydrophilic surface is more favorable for the interfacial polymerization by promoting wettability and allowing the IP (amine) solution to penetrate all surface pores. This ensures a deeper formation of the polyamide layer within the support pores, resulting in a better adhesion of the nascent PA layer. Overall, the change in molecular weight of PEI did not show any significant difference in the intrinsic properties of the supports. 2.3.2 Hollow fiber morphology For comparison, SEM images of the unmodified and 750K fibers are shown in Figure 8. A hybrid morphology of finger-like and sponge-like structures is observed from the cross-sectional images of both fibers (images unmodified-(a) and 750K-(a)). This similarity indicates that the surface modification with PEI did not affect the overall structure of the fibers, which is actually advantageous since it shows that the entire structure of the support can be independently tuned while the inner surface remains constant. Both types of fibers have a large open, open structure in the center of the fiber, which is advantageous in terms of reducing ICP (images unmodified-(b) and 750K-(b)). The difference between the inner surface of the unmodified and 750K fibers can be clearly seen by looking at the images unmodified-(c) and 750K-(c). The unmodified fibers showed a rough, uneven and defective inner surface, whereas the inner surface of the modified fiber (750K) is very smooth, uniform and defect-free. A similar surface structure was observed for the other two types of HF supports modified with PEI (2K and 25K fibers). Moreover, these similarities indicate no significant effect of the PEI molecular weight on the surface structure. It can be clearly seen that by using PEI, a rough inner surface with defects can be avoided. Surface defects are undesirable as they will cause defects (pinholes) in the selective layer and cause the IP coating to fail. Both the unmodified and 750K inner surfaces after applying IP can be seen from image (d). Figure 8d At 750K (right), a very typical and uniform PA layer can be observed with a ridge-valley structure, whereas this is not the case for the unmodified fiber. The same PA layer structure was observed for the other two types of fibers modified with PEI (2K and 25K fibers - not shown here). This result visually demonstrated that PA fabrication can be significantly improved by modifying the support with PEI regardless of its molecular weight.

[0159] To further visualize the effect of 3 wt% polymer reduction on morphology, the cross-sectional morphology of fibers 750K and M0.12 is shown in Figure 9. The 750K fiber exhibits a finger-like structure from the lumen to the center of the fiber, combined with a more open structure extending to the shell. In contrast, the M0.12 fiber has finger-like structures from both sides, with a relatively dense central portion. It is evident from this cross-sectional image that the 750K has a more open structure compared to M0.12. We argue that the dense portion of the M0.12 fiber, especially the inner one, contributes significantly to the ICP of the FO process. 2.3.3 Zeta potential of hollow fibers before IP The zeta potential of the inner surface of the HF supports was determined (Figure 10). This was done to evaluate the surface modification with PEI. In general, the three modified fibers showed more positive zeta potential than their unmodified counterparts, confirming the presence of positively charged PEI. This result is consistent with our previous study (zeta potential of M0.12 added in Figure 10) where one-step modification was performed with PEI of molecular weight 750k. This indicates that the polymer reduction of 3 wt% did not affect the PEI modification of the surface. However, the zeta potential of all three fibers does not fully reflect the zeta potential of pure PEI (as already explained in Example 1). Lower zeta potentials were observed in the investigated pH range, indicating that the support base polymer (unmodified PAI) had an impact on the final zeta potential. This means that the PEI becomes an integral part of the support and adheres properly throughout the support. 2.3.4 Pure Water Permeability (PWP) and Salt Rejection First, the pure water permeability of the fibers before IP coating was measured (Figure 11). All four fibers showed high pure water permeability, indicating that the fibers have a very open structure. This is advantageous because an open structure means low mass transport resistance, which is favorable for supports used in FO applications. Low transport resistance allows the draw solute to move faster towards the selective layer, reducing the ICP. The modified HF supports (2K, 25K, 750K) showed slightly lower permeability compared to the unmodified fibers. This indicates that the one-step modification leads to only a slight resistance to mass transport, and therefore the effect on the ICP is expected to be negligible. The PWP at 750K showed a significant increase compared to the counterpart spun with a 3% higher polymer concentration (M0.12) (Figure 11). This was 365 ± 64 (L m at 750K). -2 h -1 Bar -1 ), and 48±2 (L m -2 h -1 Bar -1 ), indicating that the structure of the freshly spun fibers (750K) became significantly more open as a result of the 3% reduction in polymer content.

[0160] The PWP was approximately 1 (L m ) after IP for all four fiber types. -2 h -1 Bar -1) (Figure 12, on the X-axis). No significant effect was observed on the molecular weight of the PEI used to prepare the modified membranes. The unmodified+IP HF membranes (squares) showed higher water permeability and greater variability than the modified fibers. This indicates that the lack of PEI on the surface made the unmodified+IP membranes less successful for IP, resulting in similarly lower NaCl rejection (Figure 12, Y-axis). Instead, all three modified HF membranes showed high success for IP, with low data deviation and NaCl rejection above 77%. Specifically, the results for M0.12 from Example 1 are added to the plot, which also shows that the data deviation is low due to the presence of PEI on its surface. However, M0.12 showed a lower PWP than 750K. This is partly due to the higher density of the support, due to the 3 wt% more polymer in the structure. 2.3.5 Penetration performance The permeation performance of the IP-coated fibers was determined in both FO and PRO modes using 1 M NaCl as the draw solution and DI water as the feed solution (Figure 13). As shown in Figure 13, all four membranes (unmodified+IP, 2K+IP, 25K+IP, 750K+IP) exhibited a permeation rate of 9 (L m -2 h -1 ) water flux. The similarity of the permeation water fluxes of the four membranes suggests that A (water permeability) is greater than 1 (L m) as obtained for our membrane. -2 h -1 Bar -1 ), it was clearly confirmed that the permeate water flux was mainly influenced by the support structure (characteristics) of the FO membrane and less by the selective layer. All four fibers had almost the same structure, porosity, and wall thickness. Thus, assuming similar ICP levels, they would have almost the same water flux. However, defects in the selective layer of the unmodified+IP membrane resulted in a higher reverse salt flux (>34 g m -2 h -1 ), whereas the reverse salt flux of the modified fiber is low (<2.5 g m -2 h -1 ) indicates that the PA layer is free of defects, which we attribute to the PEI surface modification. The 750K+IP of the membrane was 12±2 (L m -2 h-1 ) water flux, which is 4 times higher than its counterpart (M0.12) spun with 3% more polymer content, clearly indicating that the more open support structure of the 750+IP is beneficial to the resulting permeate water flux.

[0161] In the PRO mode (Figure 14), all four fibers spun in this study had a flow rate of 15 (L m -2 h -1 ), higher than the values ​​achieved in FO mode, which is typical of osmosis processes. The reason is that concentrated ICP, which occurs in PRO mode, is much less harmful than dilute ICP, which occurs in FO mode. Comparison of osmosis water flux between 750K+IP and M0.12+IP in PRO mode showed the same trend as in FO mode, with 750K+IP achieving a higher flux. Reverse salt flux in PRO mode for the membrane presented here was comparable to that in FO mode.

[0162] The structural parameters of all the membranes were calculated using equations (6) and (7) and plotted in Figure 15. In FO mode, the S-parameter was determined to be about 0.6 mm for the modified membrane, which was higher (0.75 mm) for the unmodified+IP. This may be due to the leakage properties of the selective layer that are not adequately described in equations (6) and (7). Notably, the structural parameter was higher at 1.7 ± 0.4 mm for M0.12, compared to 0.55 ± 0.05 mm for the freshly spun membrane (750K+IP). In PRO mode, the modified membranes showed higher S-parameters compared to FO mode, which was lower for the unmodified+IP membrane. This difference indicates the sensitivity of the S-parameter as a true characterization of the support. 2.4 Conclusion In this study, we demonstrated a one-step method to fabricate PEI-modified open hollow fiber membrane supports for FO. The reason for surface modification with PEI is to create a smooth and defect-free inner surface for more successful IP coating. Surface modification was performed simultaneously during spinning of the supports using three different PEIs with different molecular weights. To fabricate the open fibers, 17% less polymer was used in the polymer dope solution, which represents a 3 wt% reduction in dope compared to our previous work. The reduction in polymer concentration was surprisingly not reflected in the porosity of the freshly spun fibers, but was evident by SEM images, PWP, permeate water flux, and S-parameters. All the latter three were significantly increased. The nascent HF supports had a porosity of approximately 400 (L m -2 h -1 Bar -1 ), indicating that the support has a high openness and can promote low ICP. After application of IP, the modified fibers showed adequate NaCl rejection of more than 77%, compared to an average of 27% for the unmodified membrane, proving that the surface modification provided a defect-free surface. The permeate water flux averaged 9 (L m) in FO mode. -2 h -1 ) and 15 (L·m in PRO mode -2 h -1 ) while the reverse salt flux was very low in the modified fibers in both modes. The most significant impact of a 3% decrease in polymer content was a four-fold increase in FO water flux and a significant decrease in the S-parameter. Furthermore, variation in the molecular weight of PEI did not affect the properties of the nascent HF support, such as burst pressure, water flux, inner surface morphology, NaCl rejection, and permeation performance.

[0163] This study shows that surface modification with PEI, regardless of molecular weight, significantly improves the IP response. Furthermore, we show that targeted design can produce highly open supports with improved transmittance, which is favorable for FO. This new method and the selected polymers make it possible to fabricate very thin, open, defect-free, yet robust HF supports for FO membranes.

[0164] Various aspects and implementations have been described in connection with various embodiments herein. However, from a study of the drawings, the disclosure, and the appended claims, a person skilled in the art practicing the claimed subject matter can understand and perform other variations to the disclosed embodiments. In the claims, the word "comprising" does not exclude other elements or steps, and the indefinite article "a" or "an" does not exclude a plurality. A single processor or other unit may fulfill the functions of several items recited in the claims. The mere fact that certain means are recited in mutually different dependent claims does not indicate that a combination of these means cannot be used to advantage. The computer program may be stored / distributed on a suitable medium, such as an optical storage medium or a solid-state medium supplied together with or as part of other hardware, but may also be distributed in other forms, such as via the Internet or other wired or wireless telecommunication systems. In one aspect, the present invention may be as follows. [Aspect 1] A method for preparing a hollow fiber, comprising: a) providing a dope solution including polyamideimide (PAI); b) providing an aqueous bore solution containing polyethyleneimine (PEI); c) extruding the dope solution into a cross-sectional annular shape and discharging the bore solution at the center of the annular shape; d) reacting the PAI with the PEI, thereby forming an inner surface layer comprising a cross-linked reaction product; e) forming a polyamide thin film composite (TFC) layer on the inner surface layer containing the crosslinked reaction product by interfacial reaction of an aqueous di- or triamine compound with an organic di- or triacyl halide compound; The above method. [Aspect 2] The PAI monomer has the following chemical structure: [ka] [In the formula, Ar is [ka] is an aromatic group selected from 2. The method of embodiment 1, comprising the steps of: [Embodiment 3] The method of embodiment 1 or 2, wherein the dope solution further comprises an aprotic solvent. [Aspect 4] The method of aspect 3, wherein the aprotic solvent is selected from the group consisting of N-methylpyrrolidone (NMP), dimethylacetamide (DMAC), dimethylsulfoxide (DMSO), and dimethylformamide (DMF), or a mixture thereof. [Embodiment 5] The method of any one of embodiments 1 to 4, wherein the dope solution further comprises a polymer selected from the group consisting of polyphenylsulfone (PPSU), polyethersulfone (PES), sulfonated polyethersulfone (SPES), polysulfone (PSU), polyetheretherketone (PEEK), high temperature sulfone resin, self-reinforced polyphenylene, polybenzimidizole (PBI), polyimide (PI), polyetherimide (PEI), polyphenylene sulfide (PPS), and mixtures thereof. [Aspect 6] The method according to any one of Aspects 1 to 5, wherein the solution viscosity of the PAI measured in 25% NMP at 40° C. is 30,000 cP or less. [Aspect 7] The method according to any one of aspects 1 to 6, wherein the dope solution further comprises a glycol. [Aspect 8] The method of aspect 7, wherein the glycol is selected from ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, glycerol, or polyethylene glycol (PEG). [Aspect 9] The method according to any one of aspects 1 to 8, wherein the PEI in the bore aqueous solution has an average molecular weight (Mw) of 100,000 g / mol or more. [Aspect 10] The method according to aspect 9, wherein the PEI is branched. [Aspect 11] The method according to any one of aspects 1 to 10, wherein the aqueous bore solution further comprises an aprotic solvent. [Aspect 12] The method of aspect 11, wherein the aprotic solvent is selected from the group consisting of N-methylpyrrolidone (NMP), dimethylacetamide (DMAC), dimethylsulfoxide (DMSO), and dimethylformamide (DMF), or a mixture thereof. [Aspect 13] The method according to any one of aspects 1 to 12, wherein step c) is carried out by dry jet wet spinning. [Aspect 14] The method of any one of aspects 1 to 13, wherein the nascent hollow fiber after extrusion travels through an air gap before solidifying in the non-solvent. [Aspect 15] The method according to any one of aspects 1 to 14, wherein the air gap is 5 to 40 cm. [Example 16] The method of any one of Examples 1 to 15, wherein a plurality of hollow fibers are assembled into a module before the polyamide TFC layer is formed. [Aspect 17] The method of any one of aspects 1 to 16, wherein the di- or triamine compound is selected from m-phenylenediamine (MPD), diethylenetriamine, dipropylenetriamine, phenylenetriamine, bis(hexamethylene)triamine, bis(hexamethylene)triamine, bis(3-aminopropyl)amine, hexamethylenediamine, N-tallow alkyldipropylene, 1,3,5-triazine-2,4,6-triamine, and mixtures of these compounds. [Aspect 18] The method of any one of aspects 1 to 17, wherein the di- or triacyl halide compound is selected from trimesoyl chloride (TMC), trimesoyl bromide, isophthaloyl chloride (IPC), isophthaloyl bromide, terephthaloyl chloride (TPC), terephthaloyl bromide, adipoyl chloride, cyanuric chloride, and mixtures of these compounds. [Embodiment 19] The method according to any one of embodiments 1 to 18, wherein the aquaporin water channel is incorporated into the TFC layer. [Embodiment 20] The method of embodiment 19, wherein the aquaporin water channel is assembled into a nanostructure comprising polyethyleneimine. [Aspect 21] The method described in aspect 20, wherein the polyethyleneimine has an average molecular weight of between about 2,000 Da and about 10,000 Da, for example, between about 3,000 Da and about 5,000 Da. [Aspect 22] A method according to any one of aspects 19 to 21, wherein the aquaporin water channel is solubilized with a detergent prior to assembly into a nanostructure comprising polyethyleneimine. [Aspect 23] The method according to aspect 22, wherein the detergent is selected from the group consisting of lauryl dimethylamine N-oxide (LDAO), octyl glucoside (OG), dodecyl maltoside (DDM) or a combination thereof. [Embodiment 24] The method of embodiment 19, wherein the aquaporin water channel is provided in the vesicle prior to incorporation into the TFC layer. [Embodiment 25] The method according to embodiment 24, wherein the vesicle comprises an amphiphilic diblock copolymer of PMOXA-PDMS type and a reactive end group functionalized PDMS. [Aspect 26] The PMOXA-PDMS is PMOXA 10-40 -PDMS 25-70 26. The method of embodiment 24 or 25, wherein said compound is selected from the group consisting of: [Aspect 27] The mixture is a compound represented by the general formula PMOXA 10-28 -PDMS 25-70 and a first amphiphilic diblock copolymer of the general formula PMOXA 28-40 -PDMS 25-70 and a second amphiphilic diblock copolymer of [Aspect 28] The method of any one of aspects 24 to 27, wherein the reactive end group functionalized PDMS is functionalized with one or more of an amine, a carboxylic acid, and / or a hydroxyl group. [Aspect 29] The method according to any one of aspects 24 to 28, further comprising a PMOXA-PDMS-PMOXA type triblock copolymer. [Aspect 30] The method of any one of aspects 1 to 29, wherein the TFC layer is present on the inside of the fiber. [Embodiment 31] A hollow fiber comprising an outer support layer, an inner surface layer, and a polyamide thin film composite (TFC) layer, wherein the outer support layer comprises polyamideimide (PAI), the inner surface layer comprises a reaction product of PAI and polyethyleneimine (PEI), and the TFC layer comprises a reaction product of a di- or triamine compound and a di- or triacyl halide compound. [Embodiment 32] The hollow fiber of embodiment 31, wherein the outer support layer further comprises a polymer selected from the group consisting of polyphenylsulfone (PPSU), polyethersulfone (PES), polysulfone (PSU), polyetheretherketone (PEEK), high temperature sulfone resin, self-reinforced polyphenylene, polybenzimidizole (PBI), polyimide (PI), polyetherimide (PEI), polyphenylene sulfide (PPS), and mixtures thereof. [Embodiment 33] A hollow fiber according to embodiment 31 or 32, wherein the solution viscosity of the PAI measured in 25% NMP at 40°C is 30,000 cP or less. [Aspect 34] A hollow fiber according to any one of aspects 31 to 33, wherein the PEI has an average molecular weight (Mw) of 100,000 g / mol or more. [Aspect 35] A hollow fiber according to any one of aspects 31 to 34, wherein the PEI is branched. [Aspect 36] The hollow fiber according to any one of aspects 31 to 35, wherein the di- or triamine compound is selected from m-phenylenediamine (MPD), diethylenetriamine, dipropylenetriamine, phenylenetriamine, bis(hexamethylene)triamine, bis(hexamethylene)triamine, bis(3-aminopropyl)amine, hexamethylenediamine, N-tallow alkyldipropylene, 1,3,5-triazine-2,4,6-triamine, and mixtures of these compounds. [Aspect 37] The hollow fiber according to any one of aspects 31 to 36, wherein the di- or triacyl halide compound is selected from trimesoyl chloride (TMC), trimesoyl bromide, isophthaloyl chloride (IPC), isophthaloyl bromide, terephthaloyl chloride (TPC), terephthaloyl bromide, adipoyl chloride, cyanuric chloride, and mixtures of these compounds. [Aspect 38] A hollow fiber described in any one of aspects 31 to 37, wherein an aquaporin water channel is incorporated into the TFC layer. [Embodiment 39] A hollow fiber described in any one of embodiments 31 to 38, wherein the aquaporin water channel is assembled into a nanostructure comprising polyethyleneimine. [Aspect 40] A hollow fiber according to any one of Aspects 31 to 39, wherein the polyethyleneimine has an average molecular weight of between about 2,000 Da and about 10,000 Da, for example, between about 3,000 Da and about 5,000 Da. [Embodiment 41] A hollow fiber described in any one of embodiments 31 to 40, wherein the aquaporin water channels are solubilized with a detergent prior to assembly into a nanostructure comprising polyethyleneimine. [Aspect 42] A hollow fiber described in any one of aspects 31 to 41, wherein the detergent is selected from the group consisting of lauryl dimethylamine N-oxide (LDAO), octyl glucoside (OG), dodecyl maltoside (DDM), or a combination thereof. [Embodiment 43] A hollow fiber according to any one of embodiments 31 to 42, wherein the aquaporin water channel is provided in a vesicle. [Embodiment 44] A hollow fiber described in any one of embodiments 31 to 43, wherein the vesicle comprises an amphiphilic diblock copolymer of PMOXA-PDMS type and reactive end group functionalized PDMS. [Aspect 45] The PMOXA-PDMS is PMOXA 10-40 -PDMS 25-70 45. The hollow fiber of any one of embodiments 31 to 44, wherein the hollow fiber is selected from the group consisting of: and mixtures thereof. [Aspect 46] The mixture is a compound represented by the general formula PMOXA 10-28 -PDMS 25-70 and a first amphiphilic diblock copolymer of the general formula PMOXA 28-40-PDMS 25-70 and a second amphiphilic diblock copolymer. [Aspect 47] A hollow fiber described in any one of aspects 31 to 46, wherein the reactive end group functionalized PDMS is functionalized with one or more of an amine group, a carboxylic acid group, and / or a hydroxyl group. [Aspect 48] A hollow fiber according to any one of aspects 31 to 47, further comprising a PMOXA-PDMS-PMOXA type triblock copolymer. [Aspect 49] The hollow fiber according to any one of aspects 31 to 48, wherein the wall thickness of the hollow fiber is 0.10±0.01 mm or more. [Aspect 50] A hollow fiber according to any one of Aspects 31 to 49, wherein the inner diameter of the hollow fiber is 0.80±0.01 mm or more. [Aspect 51] A hollow fiber according to any one of Aspects 31 to 50, wherein the hollow fiber has a porosity of 75% or more. [Aspect 52] A hollow fiber obtained by the method according to any one of aspects 1 to 30. [Aspect 53] A hollow fiber module comprising a bundle of hollow fibers according to any one of aspects 31 to 52. [Embodiment 54] A hollow fiber module as described in embodiment 53, comprising a shell surrounding a bundle of hollow fibers and an inlet and an outlet connected to the lumen of the hollow fibers at each end of the bundle for passing a first solution to the lumen side of the module, and an inlet and an outlet provided in the shell for passing a second solution to the shell side of the module. [Aspect 55] A hollow fiber module described in any one of aspects 52 to 54, wherein the hollow fiber bundle is potted at each end of the module to form a liquid-tight seal between the outer surface of the hollow fibers and the shell.

Claims

1. 1. A method for preparing a hollow fiber comprising the steps of: a) providing a dope solution including polyamideimide (PAI); b) providing an aqueous bore solution containing polyethyleneimine (PEI); c) extruding the dope solution into a cross-sectional annular shape and discharging the bore solution at the center of the annular shape; d) reacting the PAI with the PEI, thereby forming an inner surface layer comprising a cross-linked reaction product; e) forming a polyamide thin film composite (TFC) layer on the inner surface layer comprising the crosslinking reaction product by interfacial reaction of an aqueous di- or triamine compound with an organic di- or triacyl halide compound, such that the inner surface layer serves as a primer for attaching the polyamide thin film composite (TFC) layer to the PAI support layer; The above method.

2. The PAI monomer has the following chemical structure: 【Chemistry 1】 [In the formula, Ar is 【Chemistry 2】 is an aromatic group selected from 2. The method of claim 1, comprising:

3. The method of claim 1 or 2, wherein the dope solution and / or the bore solution further comprises an aprotic solvent.

4. The method of claim 3, wherein the aprotic solvent is selected from the group consisting of N-methylpyrrolidone (NMP), dimethylacetamide (DMAC), dimethylsulfoxide (DMSO), and dimethylformamide (DMF), or a mixture thereof.

5. 5. The method of any one of claims 1 to 4, wherein the dope solution further comprises a polymer selected from the group consisting of polyphenylsulfone (PPSU), polyethersulfone (PES), sulfonated polyethersulfone (SPES), polysulfone (PSU), polyetheretherketone (PEEK), polybenzimidazole (PBI), polyimide (PI), polyetherimide (PEI), polyphenylene sulfide (PPS), and mixtures thereof.

6. The method according to any one of claims 1 to 5, wherein the solution viscosity of the PAI measured in 25% NMP at 40°C is 30,000 cP or less.

7. The method of any one of claims 1 to 6, wherein a plurality of hollow fibres are assembled into a module before the polyamide TFC layer is formed.

8. The method of claim 1, wherein the aquaporin water channel is incorporated into a TFC layer and assembled into a nanostructure comprising polyethyleneimine.

9. The method of claim 8, wherein the aquaporin water channels are solubilized with a detergent selected from the group consisting of lauryldimethylamine N-oxide (LDAO), octylglucoside (OG), dodecylmaltoside (DDM) or combinations thereof prior to assembly into a nanostructure comprising polyethyleneimine.

10. The method of any one of claims 1 to 7, wherein the aquaporin water channels are incorporated into the TFC layer, and the aquaporin water channels are provided in the vesicle prior to incorporation into the TFC layer.

11. The method of claim 10, wherein the vesicle comprises an amphiphilic diblock copolymer of PMOXA-PDMS type and reactive end group functionalized PDMS.

12. The method of claim 11, wherein the reactive end group functionalized PDMS is functionalized with one or more of amine, carboxylic acid, and / or hydroxyl groups.

13. 1. A hollow fiber comprising an outer support layer, an inner surface layer, and a polyamide thin film composite (TFC) layer, wherein the outer support layer comprises polyamideimide (PAI), the inner surface layer comprises a reaction product of PAI and polyethyleneimine (PEI) and is in direct contact with the TFC layer, and the TFC layer comprises a reaction product of a di- or triamine compound and a di- or triacyl halide compound.

14. 14. The hollow fiber of claim 13, wherein the aquaporin water channels are incorporated into the TFC layer.

15. 15. The hollow fiber of claim 13 or 14, wherein the aquaporin water channels are assembled into nanostructures comprising polyethyleneimine.

16. 15. A hollow fibre according to claim 13 or 14, in which the aquaporin water channels are provided in vesicles comprising an amphiphilic diblock copolymer of the PMOXA-PDMS type and reactive end-group functionalised PDMS.

17. 17. The hollow fiber of claim 16, further comprising a triblock copolymer of PMOXA-PDMS-PMOXA type.

18. 18. The hollow fiber of any one of claims 13 to 17, wherein the wall thickness of the hollow fiber is 0.10±0.01 mm or more.

19. 19. A hollow fiber module comprising a bundle of hollow fibers according to any one of claims 13 to 18, comprising a shell around the bundle of hollow fibers and an inlet and an outlet connected to the lumen of the hollow fibers at each end of the bundle for passing a first solution to the lumen side of the module, and an inlet and an outlet in the shell for passing a second solution to the shell side of the module, the hollow fiber bundle being potted at each end of the module to form a fluid tight seal between the outer surfaces of the hollow fibers and the shell.

Citation Information

Patent Citations

  • Diblock copolymer vesicles and separation membranes containing aquaporin water channels and methods of making and using them

    JP2020507456A

  • Forward osmosis hollow fiber membrane

    US20140008292A1

  • Aquaporin based thin film composite membranes

    US20140332468A1

  • Method of producing a hollow fiber membrane

    US20200078744A1